2017
DOI: 10.1111/faam.12125
|View full text |Cite
|
Sign up to set email alerts
|

The association between organizational culture and the use of management initiatives in the public sector

Abstract: This paper examines the association between five factors in O'Reilly et al. (1991) Organizational Culture Profile and the use of Activity Management (AM), Total Quality Management (TQM) and Employee Empowerment within public sector organizations. The results show that the use of AM and TQM is lower in public sector organizations than in their private sector counterparts, and is facilitated by an organizational culture of Outcome Orientation and Attention to Detail. The extent of use of Employee Empowerment is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(46 citation statements)
references
References 45 publications
1
44
1
Order By: Relevance
“…The National Institute of Standards and Technology () claims that attention to detail hinders risk‐taking attitudes and the development of novel values for the organization's stakeholders. Others studies, instead, argue that attention to detail reinforces new forms of behavior by emphasizing conformity to rules and procedures, precision and accuracy, which are crucial for quality improvement and for creating a good attitude towards new initiatives (Naveh and Erez, ; Baird and Harrison, ). Good attention to detail also provides awareness of the knowledge and activities that can help organizations to effectively deal with new challenges, which is particularly relevant in cases such as product innovation and EE measures (Sok and O’Cass, ).…”
Section: Attention To Detailmentioning
confidence: 99%
See 1 more Smart Citation
“…The National Institute of Standards and Technology () claims that attention to detail hinders risk‐taking attitudes and the development of novel values for the organization's stakeholders. Others studies, instead, argue that attention to detail reinforces new forms of behavior by emphasizing conformity to rules and procedures, precision and accuracy, which are crucial for quality improvement and for creating a good attitude towards new initiatives (Naveh and Erez, ; Baird and Harrison, ). Good attention to detail also provides awareness of the knowledge and activities that can help organizations to effectively deal with new challenges, which is particularly relevant in cases such as product innovation and EE measures (Sok and O’Cass, ).…”
Section: Attention To Detailmentioning
confidence: 99%
“…O’Reilly et al () suggest that outcome orientation comprises the OC. There have been many studies on the link between outcome‐oriented culture and performance, but the empirical evidence on this relationship is limited (Wilderom et al ., ; Baird and Harrison, ). Garnett et al .…”
Section: Outcome Orientationmentioning
confidence: 99%
“…Merchant and Van der Stede (2003, p. 133) state that tight control is characterised by comprehensive and extensive information flows within the organisation, and by 'an extremely detailed planning, budgeting and reporting system'. Similarly, Baird and Harrison (2017), in their study of public sector organisations, found that a strong culture of attention to detail emphasises formality and precision in the identification and calculation of causeeffect relationships within processes and activities. They argued that public sector organisations are more likely to be concerned with issues of formality and precision because of the requirements for accountability, and transparency of accountability, in the public sector and, consequently, the greater emphasis on formal rules and procedures.…”
Section: Attention To Detail and Erm Maturitymentioning
confidence: 99%
“…Teamwork refers to the extent to which employees within an organization co‐operate with each other and work in unison to achieve overall organizational goals. Baird and Harrison () provide evidence of the association between teamwork and the extent of use of three management initiatives, employee empowerment, total quality management and activity management. In relation to activity management, they found that teamwork was associated with the extent of use of both activity cost analysis and activity‐based costing.…”
Section: The Association Between Organizational Culture and The Adoptmentioning
confidence: 99%
“…In particular, Denison (, p. 4) states that ‘the values and beliefs of an organization give rise to a set of management practices’, and Smith () makes reference to matching management practices with cultural settings. Second, Baird and Harrison () provide empirical evidence of the association between specific dimensions of organizational culture with activity management in both the public and private sectors. Third, given organizational culture is difficult to change (Denison, ; Hofstede et al ., ), it is useful to know whether an organization's culture will facilitate EAM.…”
Section: Introductionmentioning
confidence: 99%